Evaluation of Immunophenotypic Characteristics and Quantitative Differences of Telocytes Between Invasive Breast Cancer Subtypes - Nilgün Öksel; İbrahim Halil Erdoğdu; Ömer Faruk Akgül; Merve Bulut; Özlem Yersal (Life)
Background: Breast cancer is the most commonly diagnosed neoplasm in women and is classified into different molecular subtypes based on the expression characteristics of estrogen and progesterone receptors (ERs and PRs) and human epidermal growth factor 2 (HER2, ERBB2): Luminal A, Luminal B, HER2(+), and triple-negative breast cancer (TNBC). Telocytes, a new type of stromal cell, provide structural support for the preservation of organ integrity and play a crucial role in the tumor microenvironment. In this study, we evaluated telocyte counts and expression profiles among breast cancer subtypes. Methods: The quantitative differences between telocytes in three subtypes of invasive breast cancer were assessed via immunohistochemistry, using vimentin, CD10, CD34, and c-Kit antibodies. Results: Vimentin(+), CD10(+), CD34(+), and c-Kit(+) telocyte counts were significantly higher in the Luminal and HER2(+) groups than in TNBC (p = 0.000 for vimentin, CD10, CD34, and c-Kit in Luminal vs. TNBC; p = 0.006 for CD34 in HER2(+) vs. TNBC). CD10(+), CD34(+), and c-Kit(+) telocyte counts were significantly higher in ER(+) than in ER(–) patients (p = 0.006, p = 0.000, and p = 0.009, respectively) and in PR(+) than in PR(–) patients (p = 0.018, p = 0.000, and p = 0.044, respectively). The presence of ER/c-Kit(+) telocytes was demonstrated, and c-Kit(+) telocyte counts were significantly lower in tumors larger than 5 cm than in those measuring 2–5 cm (p = 0.032). Conclusions: Our results showed quantitative differences and marker expression profiles for telocytes between different breast cancer molecular subtypes. c-Kit(+) telocytes may contribute to the regulation of tumor size.